Tata Kelola Manajemen Mesjid dan Digitalisasi Dakwah - Syahrullah Umar; Santoso Santoso (Asosiasi Dosen Akuntansi Indonesia, 2022)
The rapid development and growth of mosques is not followed by good governance, management, and application of adequate information and technology to support the realization of the vision and mission of establishing a house of worship. Partners in the proposed Community Partnership Program are partners who are not economically/socially productive, namely the Al-Hijrah Mosque in Perum Griya Utama (GTU) Pekanbaru City. The problems faced by partners at this time are the weak management of the mosque management, the low motivation and concern of the takmir and mosque's young generation in managing the mosque, and the absence of multimedia skills to support the mosque's da'wah. The solution sought in this partnership program is to hold mosque management training, motivation, character development, and multimedia skills to support the prosperity of the mosque. The output targets to be achieved from this community partnership program are good mosque management and increased partner capabilities in the multimedia field.